PRACTICAL RECOMMENDATIONS FOR EFFECTIVE JUSTICE IN GEORGIA (Law and world, 2019)
One of the most important sources of law is case law. Legal norms are like Ariadne’s thread for judges and they should come to the fair decisions in every problematic situation by this thread. The court is a body through which legal norms become alive and that’s why, court decisions are important in every legal system. Effective and uniform case law is the main and compulsory element of every democratic country.